Assessment of Tricuspid Function Atrial Septal Defect (ASD) in Patient with Echocardiography - Lalu Ahmad Asmayadi (UHAMKA Press, 2018)
Atrial Septal Defect (ASD) is the state of a hole between the right and left atrium. This condition occurs when the foramen ovale fails to close after birth, or if there is another hole between the right and left atrium due to incomplete wall closure between the two atria during gestation. Descriptive method with observational nature of the study in patients with Atrial Septal Defect (ASD) using a patients were taken directly. Echocardiography examination with patients who had a diagnosis of Atrial Septal Defect (ASD) which became the study, namely as many as patient. There is a defect between the right atrium and the left atrium causing the flow from the left atrium to flow to the right atrium towards the right ventricle so that the right heart chamber has increased volume or called dilation so that the right heart has decreased function. In the patient Ms. AKK was found to have a1.7- 2.1 cm ASD dominant bidirectional shuntsekundum. There is a defect between the right atrium and the left atrium causing the flow from the left atrium to flow to the right atrium towards the right ventricle so that the right heart chamber has increased volume or called dilation so that the right heart has decreased function. Keywords: Atrial, Septal, Defect Atrial Septal Defect (ASD) adalah keadaan lubang antara atrium kanan dan kiri. Kondisi ini terjadi ketika foramen ovale gagal menutup setelah lahir, atau jika ada lubang lain antara atrium kanan dan kiri akibat penutupan dinding yang tidak sempurna antara kedua atrium selama masa gestasi. Metode deskriptif dengan penelitian bersifat observasional pada pasien dengan Atrial Septal Defect (ASD) menggunakan pasien yang diambil secara langsung. Pemeriksaan ekokardiografi dengan pasien yang didiagnosis Atrial Septal Defect (ASD) yang menjadi penelitian yaitu sebanyak pasien. Adanya defek antara atrium kanan dan atrium kiri menyebabkan aliran dari atrium kiri mengalir ke atrium kanan menuju ventrikel kanan sehingga bilik jantung kanan mengalami peningkatan volume atau disebut dilatasi sehingga jantung kanan mengalami penurunan fungsi. Pada pasien Ms. AKK ditemukan memiliki a1.7- 2.1 cm ASD shuntsekundum dua arah dominan. Adanya defek antara atrium kanan dan atrium kiri menyebabkan aliran dari atrium kiri mengalir ke atrium kanan menuju ventrikel kanan sehingga bilik jantung kanan mengalami peningkatan volume atau disebut dilatasi sehingga jantung kanan mengalami penurunan fungsi. Kata Kunci: Atrial, Septal, Defect